2005
DOI: 10.1179/174328405x18601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fly ash particles on the mechanical properties of aluminium casting alloy A535

Abstract: Fly ash is a lightweight coal combustion byproduct (CCB) which is separated from the exhaust gases of power generating plants using suspension fired furnaces in which pulverised coal is used as the fuel. Its physical and chemical properties make it a useful construction and industrial material, especially in cement manufacturing, concrete, liquid waste stabilisation, and hydraulic mine backfill. The addition of fly ash into aluminium alloys has the potential to reduce the cost and density of aluminium castings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 59 publications
(94 reference statements)
1
30
0
Order By: Relevance
“…The increased porosity of cast aluminum composites with increased fly ash content have also been reported by other researchers [29,35,36]. The porosity formation in the composites can be attributed to the increased content of the fly ash particles, which can lead to an increase in the porosity percentages of samples.…”
Section: Density and Porosity Measurements Of Aa6063-fa Compositessupporting
confidence: 51%
See 2 more Smart Citations
“…The increased porosity of cast aluminum composites with increased fly ash content have also been reported by other researchers [29,35,36]. The porosity formation in the composites can be attributed to the increased content of the fly ash particles, which can lead to an increase in the porosity percentages of samples.…”
Section: Density and Porosity Measurements Of Aa6063-fa Compositessupporting
confidence: 51%
“…Gikunoo et al studied the influence of adding fly ash on the mechanical properties of 535 aluminum casting alloy. The results show that the increasing fly ash content of the aluminum composite increased the brittleness and porosity of the casted samples, which affected and decreased Charpy impact strength of aluminum/fly ash composites [29].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In both the above cases, the strength of the bond between the matrix and the particle is expected to play a critical role in determining wear. E. Gikunoo [2] reported that the presence of stress relieving cracks reaffirms the brittle nature of A535 alloy. Also, increasing the flyash reinforcement leads to a more brittle material.…”
Section: Literaturementioning
confidence: 99%
“…Although they have found potential applications in weight-critical components in automobile, aerospace, and defence systems [2][3][4][5], the application base of these particulate MMCs is limited by their high production cost. Recently, inexpensive aluminum alloy MMCs reinforced with fly ash, a waste by-product of coal combustion, has been engineered [6][7][8][9][10][11] to serve as a substitute for conventional particulate MMCs in several applications in order to widen the application bases of this class of MMCs. The addition of fly ash into aluminum MMCs is a value-added initiative that lowers the disposal cost of fly ash, increases energy savings by reducing the quantity of aluminum produced, and creates a healthier environment.…”
Section: Introductionmentioning
confidence: 99%